Does Practice Enhance Adaptability? The Role of Personality Trait, Supervisor Behavior, and Career Development Training - Mei, Mei; Yang, Fu; Tang, Mingfeng (Frontiers in Psychology, 2021)
Drawing upon career construction theory, we examined the mediating effect of deliberate practice (DP) on career adaptability (CA) and the effects of learning goal orientation (LGO) and supervisor incompetence accusations (SIA) as well as career development training (CDT) on DP. Using data collected from 204 Chinese PhD students in three waves over a period of 2 months, we found that individuals who were inclined to learn new skills and obtain new knowledge were more likely to deliberately practice professional activities in their fields. When a PhD student’s professional competence was questioned by his or her supervisor, the student was more prone to negative emotions and would reduce his or her effort in the development of expertise. CDT – contrary to expectations – negatively predicted DP of professional activities. One possible reason is that the participants in this study have strong autonomy so that those who really struggling are participating in training and seeking help and those who with strong professional abilities are not accessing training programs. Moreover, results showed that DP of professional activities significantly promoted PhD students to adapt to their academic circumstances. Implications for career-related practice within the academic domain are provided.